Most Popular Advertisements - Nachiappan, Shanthi (Indian Journal of Marketing, 2007)
In this article we will be seeing the three most popular ads of the recent past which were being enjoyed by you and me - India Shining, The Hutch, and last but not the least Pulliraja. We know that these advertisements were successful&it would be interesting to know the secrets of their success.